Kinematics of superdense galaxies in clusters. Issue Volume 10:Issue S309(2014) (9th February 2015) - Moretti, Alessia; Poggianti, Bianca; Bettoni, Daniela; Cappellari, Michele; Fasano, Giovanni; ,
Abstract: We present the first results obtained by analyzing the detailed kinematics of a subsample of 9 massive and compact galaxies found in the WINGS survey. The observed galaxies are very old (both luminosity and mass- weighted age are on average ≥ 10 Gyr), while they resemble more typical galaxies in the other characteristics. The total M/L ratio is determined using as free parameters the anisotropy β and the galaxy inclination i .